Transitions in loneliness in later life: the role of social comparisons and coping strategies - Deborah Morgan (Ageing and Society, 2022)
This study explored the coping strategies and social comparisons used by older adults on different loneliness trajectories (decreased loneliness, stable loneliness and degenerating loneliness). The adaptive consequences of social comparison in later life are recognised as an important strategy for preserving life satisfaction regardless of age-related losses. Coping strategies are also important in managing loneliness. Narrative interviews were conducted with lonely older adults (N = 11) who had participated in Wave One of the Maintaining Function and Well-being in Later Life Study Wales (CFAS Wales). The study found key differences in the coping strategies employed by older adults on different loneliness trajectories. Differences in coping styles between those who reported decreased loneliness and those who were chronically lonely stemmed from perceptions as to whether loneliness was modifiable or not. Different types of social comparison were also found to modulate the loneliness experience. The findings indicate that higher-order strategies (problem, emotional and meaning focused) are not distinct entities but are part of a dynamic process. The management of loneliness in later life may be dependent on several factors, including older adults’ interpretations of the cause of loneliness. These interpretations will have implications for interventions aimed at alleviating chronic loneliness, where the focus may have to be on changing older adult's perceptions of unmodifiable loneliness.